Reformulation Of Islamic Educational Leadership In The Era Of Disruption - Zainal Azman; Supriadi; Joni Helandri (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
Indonesia’s pesantren face the critical challenge of navigating digital era (Industry 4.0) disruption. Their leadership must manage rapid technological adoption to ensure institutional growth without compromising foundational Islamic identity. This study addresses how to successfully harmonize modernization with tradition. This study aims to identify the opportunities and challenges facing pesantren amid digital transformation and to examine the crucial role of leadership in managing this change. This study employed a literature review method with a descriptive analytical approach, analyzing scholarly sources to uncover key patterns and findings regarding digital dynamics and leadership strategies in pesantren. The findings are guided by visionary leadership, pesantren have great potential to transform into a modern and progressive Islamic education center. Through an effective balance between the adoption of technology and the preservation of fundamental Islamic values, pesantren can continue to contribute to shaping a generation that is faithful, knowledgeable, and globally competitive.